Analysis of Errors Made by Children with Hearing Impairment - NAIR, PRITHI (THE PRIMARY TEACHER, 2015)
Making mistakes in mathematics is common and teachers usually ignore the mistake thinking children will overcome it. However, if a pattern of error is observed, it is an indication of some underlying problem in learning mathematics and should be addresses. The present study aims at identifying and addressing the errors made by children with hearing impairment in Arithmetic Diagnostic Test (ADT) for Grade -IV. The errors were analysed qualitatively for mathematical concepts like numeral concept, addition, subtraction, multiplication and division. The errors were classified as in-correct operation, poor concept, non-performers and correct response. The results of analysis revealed that children were able to attempt simple task which had concrete representation (count and write), single digit addition. However, the number of errors increased as the level of difficulty increased. The probable reasons identified for the errors were inability to understand verbal instruction, poor concept of place value, not able to read and follow instruction due to poor reading skill. The common errors identified for addition, subtraction were carrying over and borrowing problem. Multiplication and division were the poorly attempted task and word problems were not attempted or least attempted across all the concepts. The implication of the findings highlights developing a strong number concept among the children, developing their language and reading skills and empowering teachers for error analysis thus paving way for good remedial instruction.